Using zeolite, molasses, and PGP microorganisms to improve apatite solubility and increase phosphorus uptake by Sorghum bicolor L. (Speedfed cultivar) - Fereshteh Hashemi; Roya Zalaghi; Naeimeh Enayatizamir (Scientific Reports)
Abstract This study investigated the effect of the application of apatite (Ap), some amendments (zeolite and molasses), and some microbial inoculations (plant-growth-promoting microorganisms; including Claroideoglomus etunicatum, Serendipita indica, Enterobacter cloacae, and Brevundimonas sp) on P in organic (Po) and P in inorganic (Pi) fractions, alkaline phosphatase activity, and Sorghum bicolor L. (Speedfed cultivar) growth in sandy soil with pH 7.8. A factorial pot experiment in a completely randomized design was performed with three replications, using microbial inoculants (non-inoculated, Claroideoglomus etunicatum, Serendipita indica, Enterobacter cloacae, and Brevundimonas sp) and four amendments levels (control, Ap, Ap-Z (Ap-zeolite), and Ap-M (Ap-molasses)). Ap application increased all mineral fractions of P as follows: Ca10-P > Ca8-P > Ca2-P > Olsen P. Application of Ap-Z led to the increase of Olsen-P and Ca2-P to 1.21 and 1.67 fold as compared to Ap. Po was very low in soil, which was increased significantly with the application of amendments. In Ap-M treatments, the moderately labile Po and moderately non-labile Po increased significantly as compared to Ap treatments. Application of Ap-Z reduced pH more than Ap and Ap-M treatments. Furthermore, the largest amount of alkaline phosphatase was observed in Ap-M treatments. These findings show various mechanisms of microorganisms for using Ap in their metabolism in the presence of different amendments. Microbial inoculation (especially C. etunicatum) resulted in a decrease in pH and an increase in alkaline phosphatase. Application of amendments (Ap-Z and then Ap-M) resulted in better growth of Sorghum compared to control and Ap treatments. Application of Ap with zeolite and then molasses along with inoculation with plant-growth-promoting microorganisms were two useful solutions to improve the productivity of sandy soils.